2006
DOI: 10.1159/000093077
|View full text |Cite
|
Sign up to set email alerts
|

<i>Acanthamoeba </i>Keratitis and Contact Lens Disinfecting Solutions

Abstract: Objectives: To report cases of culture-proved Acanthamoeba keratitis in Greece over a 10-year period and to evaluate the effectiveness of the commonly used commercial contact lens disinfecting systems in clinical cases of Acanthamoeba keratitis. Material and Methods: During the years1994–2004, 45 contact lens wearers and 3 non-contact lens wearers presenting with symptoms and signs of keratitis underwent corneal sampling. The scrapings obtained were inoculated directly onto appropriate culture media for bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(8 reference statements)
1
18
0
1
Order By: Relevance
“…However, propylene glycol is not unique to AMOCMP and is an ingredient of at least 1 other multipurpose solution, as well as several brands of artificial tears. Published results on the performance of multipurpose solutions, including AMOCMP, against Acanthamoeba organisms have shown varying efficacy ( 14 16 ). Assessment of anti- Acanthamoeba solution efficacy is limited by a lack of standardized testing methods ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, propylene glycol is not unique to AMOCMP and is an ingredient of at least 1 other multipurpose solution, as well as several brands of artificial tears. Published results on the performance of multipurpose solutions, including AMOCMP, against Acanthamoeba organisms have shown varying efficacy ( 14 16 ). Assessment of anti- Acanthamoeba solution efficacy is limited by a lack of standardized testing methods ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ineffective contact lens disinfecting solutions is strongly linked to the threat of Acanthamoeba infection in contact lens wearers. A 10-year survey (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) 62 showed that Acanthamoeba was isolated in contact lenses and contact lens disinfecting solutions in all cases of Acanthamoeba keratitis. The one-step 3% hydrogen peroxide and multipurpose solutions were found to be ineffective in killing Acanthamoeba cysts and trophozoites, as well as bacteria and fungi.…”
Section: Mechanical Ways Used In Contact Lensmentioning
confidence: 99%
“…2 Unfortunately, the susceptibility of Acanthamoeba trophozoites, but particularly the amoebic cysts, is limited to a small number of chemical compounds. 33,34 Propamidine isethionate (Brolene [not yet FDA approved in the U.S.], Aventis, Bridgewater, NJ), polyhexamethylene biguanide (PHMB), chlorhexidine, and hexamidine have shown effectiveness against the trophozoite and, to a degree, the cyst. 33 There is some optimism, however, that newly developed biguanides (alexidine) and antifungal agents (caspofungin) may have greater effect against the Acanthamoeba cyst.…”
Section: Occurrence Of Acanthamoeba Keratitismentioning
confidence: 99%